2019
DOI: 10.1016/j.ebiom.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the miR-25-IMPA2 axis promotes metastatic progression in clear cell renal cell carcinoma

Abstract: Background The molecular mechanism underlying clear cell renal cell carcinoma (ccRCC) metastasis remains unclear. We therefore aimed to elucidate the role of IMPA2 in ccRCC metastatic progression. Methods Using the Cancer Genome Atlas (TCGA) database and immunohistochemistry (IHC) staining, we investigated differences in IMPA2 mRNA and protein expression, as well as their clinical relevance, in ccRCC. To investigate the function of IMPA2 in ccRCC metastasis, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…However, there is only one published article clearly demonstrated the relationship between IMPA2 expression and cancer progression. Lin et al recently showed that IMPA2 downregulation constitutes a novel signature for cancer metastasis and poor outcomes in ccRCC 15 . On the contrary, our data of RNA sequencing (RNA-seq) showed an obvious upregulation of IMPA2 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is only one published article clearly demonstrated the relationship between IMPA2 expression and cancer progression. Lin et al recently showed that IMPA2 downregulation constitutes a novel signature for cancer metastasis and poor outcomes in ccRCC 15 . On the contrary, our data of RNA sequencing (RNA-seq) showed an obvious upregulation of IMPA2 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, French et al 14 found that IMPA2 expression might affect accumulation of methotrexate polyglutamates (MTXPGs) in leukemia. In addition, Lin et al 15 indicated that IMPA2 downregulation leads to poor outcomes in clear cell renal cell carcinoma (ccRCC). This is contrary to our speculation on the role of IMPA2 in cervical cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 30% of RCC subtypes, such as chromophobe and papillary RCC, are generally indolent (3). Surgery is the most effective treatment for ccRCC, as chemotherapy and radiotherapy are not as successful in controlling its progression; however, ~25% of clinical patients with ccRCC will develop metastatic disease despite curative surgical removal of the primary tumor (4). The overall 5-year survival rate of RCC patient is 5-10%, with a median survival of only ~13 months (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that IMPA2 (inositol monophosphotase 2) leads to decreasing p-mTORC1 levels in ccRCC cells, and thus could be a biomarker for guiding the use of mTOR inhibitors to combat metastatic ccRCC in clinical practice [ 67 ]. Indeed, IMPA2 underexpression in ccRCC diminishes the expression of N-cadherin and Slug, and sabotages tumor metastasis by downregulating miR-25-3p [ 68 ]. Dysregulated cellular energetics is one of the hallmarks of RCC and of multiple cancers [ 47 ].…”
Section: Mirnas Act As Oncogenes In Renal Cancermentioning
confidence: 99%